The Haunted States of America Gothic Regionalism in Post-war American Fiction. - Morgart, James (Gothic literary studies., 2022)
The Haunted States of America: Gothic Regionalism in Post-war American fiction focuses on existing regional Gothic strains to examine how the anxieties, fears and concerns illustrated in the works of several post-World War II writers can be best understood through regional history and identity.